Energy metabolism as a regulator of ferroptosis. Issue 22 (16th November 2020) - Ma, Yanhong; Han, Fei; Min, Junxia; Lin, Weiqiang
ABSTRACT: Ferroptosis is a newly identified form of cell death that is regulated by many metabolic pathways, including iron, lipid and amino acids. Recent two studies reveal that the mitochondria and energy stress could also mediate ferroptosis. Gao et al. report that mitochondria play an essential role in ferroptosis induced by cysteine deprivation. In addition, Lee et al. show that energy stress depressed ferroptosis partly through activation of AMP-activated protein kinase. These findings provide potential therapeutic strategies for treating ferroptosis-related diseases, such as cancer, tissue injury and neurodegenerative diseases.